Pengaruh Pelatihan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Pusat Kegiatan Belajar Masyarakat Ar-Rahman - Raden Yeti Sumiaty, Sam Cay (Journal of Innovative and Creativity, 2025)
This study examines the influence of training and work motivation on employee performance at the Ar-Rahman Community Learning Activity Center (PKBM). Using a quantitative approach, data were collected through questionnaires distributed to 30 employees and analyzed using multiple linear regression with SPSS 26. The results indicate that both training and work motivation significantly affect employee performance. Training shows a strong positive impact (β = 0.47, p < 0.01), while work motivation also demonstrates a significant positive effect (β = 0.43, p < 0.01). Together, these variables explain 67% of the variance in employee performance (R² = 0.67). The findings highlight the critical role of structured training programs and motivational strategies in enhancing employee productivity in non-formal educational settings. This research recommends that PKBM management implement regular competency-based training and non-material reward systems to sustain employee performance. The study contributes to human resource management practices in community-based education by emphasizing the integration of capacity development and motivational approaches.